Suggestions for Enhancing the Spatiotemporal Characterization of Retinal Degeneration in the MNU-Induced RP Model [Letter] - Chen C; Gao H; Guo X; Wei W (Journal of Inflammation Research)
Chen Chen,1 Haoming Gao,2 Xiuli Guo,2 Wei Wei3 1Department of Ophthalmology, Dalian Women and Children’s Medical Group, Dalian, Liaoning, People’s Republic of China; 2People’s Liberation Army 32183 Troops Hospital, Baicheng, Jilin, People’s Republic of China; 3Armed Police Force First Mobile Corps Hospital, Baoding, Hebei, People’s Republic of ChinaCorrespondence: Wei Wei, Armed Police Force First Mobile Corps Hospital, No. 1, Xinghua East Road, Beicheng District Street, Dingzhou, Baoding, Hebei, 073000, People’s Republic of China, Email 639092@qq.com